BIMBINGAN DAN KONSELING DALAM PENDIDIKAN FORMAL - Vianda, Debi (Jurnal Al-Taujih : Bingkai Bimbingan dan Konseling Islami, 2015)
Viewed from the perspective of the profession, the development of guidance and counseling in the country has not shown the progress normally as an independent profession. Problems guidance and counseling are always facing the dynamics of this profession. Guidance and counseling mandated as one component of education in schools memandirikan counselee (learners), have not been able to carry out the mandate. Contributions school counselors (teacher BK) dyed ability to develop competence is not yet a practical reality in guidance and counseling services in schools. On the other hand, bureaucratic policy raises broad opportunities in this profession downgrades. As a profession, the performance of guidance and counseling services should meet the four elements, namely the fundamental theory, validated standard practice, the autonomy of the profession, and professional organizations are credible. Some scientific activities are carried out in this study to improve the competence of school counselors (teacher BK) is a research, seminars, workshops, workshops, trainings, discussion panels, and similar activities that scale local, national, regional, and international, for the future guidance and counseling as an independent profession.